92.0k views
5 votes
Solve using substitution.
y = 8x + 7
y = -8x - 9

Solve using substitution. y = 8x + 7 y = -8x - 9-example-1
User Gavin King
by
5.8k points

2 Answers

3 votes

Answer:

(-1,-1)

Explanation:

1) since both equations are equal to y, we can substitute the value of "y" in one equation to the value of y in another:

8x+7=-8x-9

combine like terms:

8x+8x=-7-9

16x=-16

x=-1

now substitute "x" as -1

8(-1)+7=-1

hence

x=-1

y=-1

so (-1.-1)

User Roshambo
by
7.0k points
5 votes

Answer:

(-1,-1)

Explanation:

User Mcccclean
by
5.6k points